Delamination of the Annulus Fibrosus of the Intervertebral Disc: Using a Bovine Tail Model to Examine Effect of Separation Rate - Briar, K. Josh; McMorran, John G.; Gregory, Diane E. (Frontiers in Bioengineering and Biotechnology, 2022)
The intervertebral disc (IVD) is a complex structure, and recent evidence suggests that separations or delamination between layers of the outer annulus may contribute to degeneration development, a common cause of low back pain The purpose of the present experiment was to quantify the mechanical response of the layer-adjoining interlamellar matrix at different rates of separation. Understanding the rate-dependency of the interlamellar matrix, or the adhesion between adjacent layers of the disc, is important as the spine experiences various loading velocities during activities of daily living. Twelve discs were dissected from four bovine tails (three extracts per tail). Two multi-layered annulus samples were collected from each IVD (total=24, mean bond width=3.82±0.96mm) and randomly assigned to a 180° peel test at one of three delamination rates; 0.05mm/sec, 0.5mm/sec, or 5mm/sec. Annulus extracts were found to have similar maximal adhesion strengths (p=0.39) and stiffness (p=0.97) across all rate conditions. However, a significant difference in lamellar adhesion strength variability was observed between the 5mm/sec condition (0.96 N/mm ± 0.31) when compared to the 0.5mm/sec (0.50 N/mm ± 0.19) and 0.05mm/sec (0.37 N/mm ± 0.13) conditions (p<0.05). Increased variability may be indicative of non-uniform strength due to inconsistent adhesion throughout the interlamellar matrix, which is exacerbated by increased rates of loading. The observed non-uniform strength could possibly lead to a scenario more favourable to the development of microtrauma, and eventual delamination.